Prolonged antibiotic prophylaxis use in elective orthopaedic surgery – a cross-sectional analysis - Rohrer, Felix; Maurer, Anita; Noetzli, Hubert; Gahl, Brigitta; Limacher, Andreas; Hermann, Tanja; Bruegger, Jan (BMC musculoskeletal disorders, 2021)
Purpose Surgical antibiotic prophylaxis (SAP) prevents surgical site infections (SSI). In orthopaedic surgery, the use of prolonged SAP (PSAP) has been reported in daily routine, despite guidelines advising against it. Therefore, we asked: What is the proportion of PSAP use, defined as administration of SAP ≥24 h after elective orthopaedic surgery? Are there patient- and surgery-related predictors of PSAP use? Methods This cross-sectional analysis investigated 1292 patients who underwent elective orthopaedic surgery including total joint arthroplasties at one Swiss centre between 2015 and 2017. Patient comorbidities, surgical characteristics and occurrence of SSI at 90 days in PSAP group were compared to the SAP group (< 24 h post-operative). Results PSAP use was 12% (155 of 1292). Patient-related factors associated with PSAP compared to the SAP group included older age (63 vs. 58y; p < 0.001), higher BMI (29 vs. 27 kg/m 2 ; p < 0.001), ASA classification ≥3 (31% vs. 17%; p < 0.001) and lung disease (17% vs. 9%; p = 0.002). Surgery-related factors associated with PSAP were use of prosthetics (62% vs. 45%; p < 0.001), surgery of the knee (65% vs. 25%; p < 0.001), longer surgery duration (87 vs. 68 min; p < 0.001) and presence of drains (90% vs. 65%; p < 0.001). All four SSI occurred in the SAP group (0 vs. 4; p = 1.0). Surgeons administered PSAP with varying frequencies; proportions ranged from 0 to 33%. Conclusion PSAP use and SSI proportions were lower than reported in the literature. Several patient- and surgery-related factors associated with PSAP use were identified and some were potentially modifiable. Also, experienced surgeons seemed to implement differing approaches regarding the duration of SAP administration.